POLITICAL THREATS ONPERSONAL DETERIORATION THROUGH TRENDSETTING OF SARA EVENTS - Wahyudi, W (Jurnal Partisipatoris, 2020)
This article analyzes the phenomenon of socio-political ?crime?, which occursand develops in the state life of Indonesia. The form of this phenomenon is socialnegativism; a concept of which views the different socio-cultural attributes apartfrom itself as negativity. The ideology of this concept resulted in personalitydeterioration through the trendsetting events with a background of ethnicity,religion, race, and inter-group relation on social media. This portrait of the socialworld is very much in contradiction with the character or identity of Indonesianswho uphold the values and norms of Pancasila and the 1945 Constitution. Thepersonality deterioration politics aims at destroying the integrity of politicalcontestants, both generally and in particular, therefore, it can widen the road to itssuccess in gaining power supremacy. The emergence of personality deteriorationpolitics is due to the weakness of civil society in Indonesia. On one side, theIndonesian public still depends significantly on the state, and on the other hand,it does not have full freedom to avoid the nepotism as a common practice in thecountry. This weakness of Indonesian civil society has resulted in the inability ofmulticulturalism to develop in the country.The particular situation and condition have caused the more common practice ofsocial negativism and personal deterioration. These pathogenic social phenomena, bothmicro and macro, has become a serious threat towards the life of the nation, which aims atcreating prosperity and serenity for all its citizen.